Intracranial arachnoid cyst in a 28-year-old man. A clinical case with a fatal outcome - N. V. Krakhmal; S. S. Naumov; K. S. Vtorushin; T. R. Minekhanov; M. V. Zavyalova; S. V. Vtorushin (Бюллетень сибирской медицины)
Most intracranial arachnoid cysts are thought to be non-tumorous, congenital, intra-arachnoid cerebrospinal fluid collections that account for about 1% of all intracranial space-occupying lesions. In children, the prevalence of this pathology is 2.6%; in adults, it reaches 1.4%. The disease is more often registered in men. Most often arachnoid cysts are supratentorial. Their most common locations are in the middle cranial fossa and the retrocerebellar cistern. Less often they can be detected on the convexity of the brain hemispheres; however, cases of arachnoid cysts at more unusual sites have also been described, including in newborns. The pathology is often characterized by an asymptomatic course, while certain symptoms may have an acute onset, which is due to compression of brain structures caused by the large cyst size.This article describes a clinical case of a large intracranial arachnoid cyst in a 28-year-old man. It was not verified in the antemortem diagnosis, but was revealed according to the autopsy findings (macroscopic features of the cyst, histologic presentation with specific morphological changes, and findings of computed tomography of the cerebral hemispheres).